Art through Wikidata: A Digital Curation Perspective - Sant, Toni; Tabone, Enrique (Mimesis Journal, 2024)
Digital Curation Lab Director Toni Sant and the artist Enrique Tabone started collaborating on a research project exploring the visualization of specific datasets from Wikidata for artistic practice in 2019. The research was initiated by Tabone through a Wikidata exploration of gender representation in the University of Salford’s Art Collection. Eventually, she developed an inquiring model for application on other art or museum collections. During the period 2021–2023, datasets on which this approach has been applied include about a hundred university art collections across the United Kingdom, as well as Heritage Malta’s collection of prehistoric female figurines, held at two museums in Malta and Gozo. For DRHA 2023, the project brought together the research work conducted over the previous years toward a coherent conclusion. This was demonstrated through a sound art installation accompanied by physical objects, both created by Tabone.